Universidade integrada que se integra a cidade: a sustentabilidade das áreas verdes de uso público da Cidade Universitária da UFRJ - Rodrigues, Vera do Carmo (2021)
This study aims to contribute to the reflection on the relevance of the green areas of the University City and urban infrastructure in the updating of the Master Plan of the Federal University of Rio de Janeiro. In this regard, the research glimpses the Plan as an opportunity to reduce the negative human impacts arising from actions (or inertias) resulting from previous plans, focusing on socio-environmental sustainability, valuing the natural attributes of Ilha do Fundão and the best offer of spaces for outdoor activities, especially after the COVID-19 pandemic. The methodology adopted in the research consisted mainly of historical bibliographic survey, on-site visits with photographic records and application of the Environmental Quality Index of Green Areas (IQA) of the Campus. The time frame was 2009, when the University opted for its integration of the road network to the City of Rio de Janeiro, emblematically eliminating the physical barrier represented by the fence that separated them and the UFRJ Real Estate Valorization Project – Viva UFRJ, for its contemporaneity and indissociability with the updating of the UFRJ Master Plan. The systemic analysis of the geoenvironmental unit (urban infrastructure, landscape quality and green areas) of the university campus confirmed its potential for public use, provided that it is managed with sufficient funds to maintain the spaces.